(untitled) (Economics and region, 2025)
This article explores global practices in implementing regional and interregional projects, which typically emerge as responses by countries and regions to global (including geopolitical) challenges, the growing influence of innovation, and the demand for breakthrough technological solutions. It traces the development of major innovation-driven initiatives across European and Asian nations, highlighting the strategies used to implement them and their impact on reshaping international competition and transforming regional, interregional, and global relations. Special attention is given to key European Union projects focused on advancing disruptive innovations, sustainable development, and digital transformation. The EU’s contemporary innovation policy aims to address pressing societal, environmental, and economic challenges through approaches such as Industry 4.0, smart specialization, and sustainability. This policy is supported by the formation of innovation ecosystems at both regional and interregional levels and systematic support for startups and SMEs working on breakthrough technologies. Projects such as SMARTY exemplify efforts to foster green and digital transitions, contributing to the broader development of the European innovation ecosystem and promoting interregional cooperation. The paper also examines the evolution and current status of China’s Belt and Road Initiative (BRI), identifying its major accomplishments and emerging difficulties. Factors such as the trade conflict with the United States and the COVID-19 pandemic have prompted China to adopt stricter criteria for project selection under BRI, prioritizing initiatives of strategic and economic significance. As a result, China has strengthened its role as a major global investor and creditor, particularly within the Asian region. The article further evaluates BRI’s potential trajectory in Europe and considers alternative initiatives launched by the EU, the United States, G7 countries, and others aiming to counterbalance China’s global economic influence. Finally, the article reviews the newly announced "Central Asia +" framework—including the “EU–Central Asia” initiative introduced in 2025—which may pave the way for a renewed structure of regional cooperation in Asia.